“Atlantic Еxpansion” and International Legal Basis for Reunification of the Crimea with Russia - E. Voronin (Международная аналитика, 2018)
Transatlantic expansion in Europe in order to move NATO’s strategic positions to the borders of Russia together with the inspirited Washington-Brussels duo, the “Ukrainian crisis”, is the main destabilizing factor for the security in the European region. In context of preventing threats to the Russian Federation it should be perceived through the declaration of will by the people of the Crimea, who used their right for self-determination and for their future as part of the Russian state and return of the Crimea to Russian fatherland. The article includes “three groups” of international legal grounds for the reunification of the Crimea with the Russian Federation: territorial succession, secession (but not annexation) and a territorial title. Justification for a fully legal inclusion of the Crimea into Russia as a state of historical sovereignty, unlike Ukraine, which historically never existed as an independent state, without legal claim for the Crimea, which was part of the Ukraine due to an anticonstitutional voluntarism of the soviet ruling of that time.